1970
DOI: 10.1139/y70-071
|View full text |Cite
|
Sign up to set email alerts
|

Renin activity and norepinephrine, cation, and water contents of cardiovascular tissue of dogs with congestive heart failure and ascites

Abstract: 1970. Renin activity and norepinephrine, cation, rind water contents sf cardiovascular tissue of dogs with congestive heart failure and ascites. Can. J. Physiol. Pharnaacol. 48, 463468. Six dogs with congestive heart failure and ascites were studied for ( a ) renin, norepinephrine, water, sodium, potassium, calcium. and lrnagnesium contents in cardiovascular tissues; ( h ) plasma renin activity and renin substrate; ( c ) renal renin activity, juxtaglomerular index, and glucose-6-phosphate dehydrogenase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…SH rat by manipulation of dietary sodium confirms the results of others (Aoki, Yamori, Ooshima & Okamoto, 1972). A significant increase in arterial renin content of the dog has also been observed after sodium restriction (Hayduk et al, 1970b). In the present study, plasma renin did not fall in animals receiving a high sodium diet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SH rat by manipulation of dietary sodium confirms the results of others (Aoki, Yamori, Ooshima & Okamoto, 1972). A significant increase in arterial renin content of the dog has also been observed after sodium restriction (Hayduk et al, 1970b). In the present study, plasma renin did not fall in animals receiving a high sodium diet.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of renin-like enzymes has been reported in arterial tissue from hog (Gould, Skeggs & Kahn,1964), rat (Genest, Simard, Rosenthal & Boucher, 1969) and dog (Hayduk, Brecht, Vladutiu, Simard, Rojo-Ortega, Belleau, Boucher & Genest, 1970b). Although there is some controversy as to whether or not a true renin-like enzyme exists in extrarenal tissues (Day & Reid, 1976), it has been demonstrated (Gould et al, 1964) that the renin-like enzyme of hog aortic tissue, partially purified by salt precipitation, has the same p H optimum and reaction kinetics as the kidney enzyme.…”
Section: Introductionmentioning
confidence: 85%
“…The etiology of the altered fluid balance in CHF can be attributed to both hemodynamic (1,3,5,7) and hormonal factors (4,(8)(9)(10)(11). Evidence has been presented by several investigators that the secretion of antidiuretic hormone (ADH) may be altered during CHF or related disease states (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that vascular resistance was reduced in hamsters with heart failure but not in hamsters with myopathy alone is consistent with this suggestion and presents the possibility that absence of augmented activity of terminal vascular sympathetic nerve endings may be characteristic of this model of heart failure or various other models of "highoutput" failure but not of the more common forms of 'low-output" failure with high vascular resistance However, several observations in other models of heart failure make this possibility unlikely. Hayduk et al (9) have reported that in dogs with lowoutput failure produced by tricuspid avulsion the norepinephrine content of arteries is normal or decreased. Furthermore, recent studies by Schmid et al (20) have indicated that resting sympathetic tone of blood vessels in the extremity is normal in dogs with heart failure and that responses to direct nerve stimulation are normal or reduced.…”
Section: Discussionmentioning
confidence: 99%